Efecto de los post en Facebook de los principales candidatos españoles en las elecciones generales de 2016 sobre la polarización de la sociedad - Abejón Mendoza, Paloma; Carrasco Polaino, Rafael; Garralón, Miguel L. (Historia y Comunicación Social, 2019)
According to Hallin and Mancini (2004), the Spanish media system fits in the Polarized Pluralist Model. This model shows a situation where the media don´t act as an independent element of the politic power. Instead of that, the media give themselves up to proselytism and the attack to the opponent. The objective of this investigation is to prove how the social media Facebook works in relationship with the political polarization phenomenon. It will be analysed qualitatively the post of the four leading candidates to the Spanish government in the last general elections (June 26th, 2016) during one week of the electoral campaign (from the 19th to 25th of June). It will be considered the polarization level generated by the post attending to the number of the sent comments.